Sustaining The Culture of Excellence: A Systematic Review of High-Performance School Grants Utilization in Maintaining Educational Achievements - Dhinar Sri Rustiana; Slamet Subiyantoro; Kusdianto Kusdianto (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
In recent years, education policies globally have shifted towards performance-based funding (PBF) schemes, rewarding high-performing schools with additional grants to sustain their quality. In Indonesia, this is manifested through the BOS Kinerja Prestasi. However, limited research synthesizes how these rewards are strategically utilized to maintain a culture of excellence rather than merely funding short-term activities. This study aims to systematically review global literature on the utilization of achievement-based school grants and identify managerial strategies that effectively sustain educational achievements. A Systematic Literature Review (SLR) was conducted using the PRISMA protocol. Data were sourced from Scopus, ERIC, and Google Scholar (2020–2025) using keywords: "performance-based funding," "school reward grants," "sustaining school improvement," and "high-performing school culture". Twenty articles meeting the inclusion criteria were analyzed. The synthesis reveals three dominant themes in effective grant utilization: (1) Investment in sustainable human capital development through teacher training, (2) Strengthening the school ecosystem and climate to foster student engagement, and (3) Digital transformation for talent management. Schools that allocate grants for long-term capacity building show higher sustainability in achievement compared to those spending on consumable resources. It is concluded that financial rewards act as a catalyst, but managerial prudence in allocation determines the sustainability of excellence.